Climate Change Impacts on Agriculture and Water Resource Management in the North China Plain. Issue 1 (1st April 2022) - Lin, Yanwei; Li, Guangyu
Abstract: North China Plain (NCP) is a main agricultural production region in China, dominated by a summer maize-winter wheat double cropping system. However, the grain yield highly depends on groundwater extraction to fulfil the irrigation demand. Additionally, the warming and drying tendency under climate change will further challenge water resource availability and agricultural productivity. This study applied modelled regional precipitation and temperature within the East Asia domain from the Coordinated Regional Climate Downscaling Experiment to derive climate change indicators and quantify future water resource utilisation. Results show a 30% increase in water irrigation demand (IWD) for growing maize in Jiangsu Province and a slight decrease in central Shandong Province. While for wheat, IWD decreases by 3-24% over the NCP except for northern Hebei Province and northern Shandong Province. Therefore, we suggest reducing agricultural fields for summer maize in southern NCP and winter wheat in northern NCP, and intensifying cultivation in central Shandong Province. Mann-Kendall statistics indicate an indistinct trend for IWD but a significant increase in crop evapotranspiration (ETc) during 2021-2050, highlighting the necessity to cope with rising ETc and apply varieties with high stress-tolerance to release irrigating water intensity under future climate change.